2014
DOI: 10.1007/s00414-013-0959-8
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ligature strangulation using gymnastics bands

Abstract: Suicidal ligature strangulation is a rare event. The most important issue to solve in the investigation is whether it is a case of homicide or suicide. The characteristics of suicidal ligature strangulation are summarized by Koops and Brinkmann with the emphasis on the nature of the ligature instrument(s). In this article, we present two cases of self-strangulation with an almost identical modus operandi using gymnastics bands. The autopsy findings and the nature of the ligature in these cases are depicted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Suicide by self‐strangulation is unusual but not rare. Case reports and case series have been published in the scientific literature . Our case is an interesting case of suicide by self‐strangulation, which culminated into partial hanging due to a unique mechanism used for the process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Suicide by self‐strangulation is unusual but not rare. Case reports and case series have been published in the scientific literature . Our case is an interesting case of suicide by self‐strangulation, which culminated into partial hanging due to a unique mechanism used for the process.…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of various case reports and case series published on self‐strangulation indicates that the victims of these types of suicide are predominantly male and are above 30 years of age. The ligature used in these cases are a twin, cable tie, hemp rope, scarf, fabric belt, a sleeve of a shirt, nylon rope, dressing gown cord, underpants elastic, telephone wire, pantyhose, wire cloth hanger, rubber band, shoelace, elastic gymnastic bands and waist belt.…”
Section: Discussionmentioning
confidence: 99%
“…W przypadku zadzierzgnięcia zacisk wywoływany jest jednak w inny sposób, a domyślną przyczyną zgonu jest zwykle zabójstwo [3]. Dławienie, kneblowanie, przyduszanie czy duszenie rzadko ma charakter samobójczy, a samozadzierzgnięcie prawie zawsze budzi podejrzenia ze względu na rodzaj metody i zastosowany typ materiału zaciskającego [4][5][6][7][8][9]. Zadzierzgnięcie polega na wywołaniu ucisku szyi za pomocą rąk lub zacisku [2,10].…”
Section: Wstępunclassified
“…Choking, gagging, smothering, or strangulation are rarely suicidal. However self-strangulation is almost always suspicious due to application of the type of method and ligature material used [4][5][6][7][8][9]. Strangulation is compression of the neck by use of hands or a ligature [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…Self‐strangulation by ligature is usually prevented, when a constant force is not maintained around the neck to obstruct venous blood flow until death . However, different authors have reported various suicidal ligature strangulation techniques adopted by the decedents . The present case report describes a rare suicidal ligature strangulation case of a 51‐year‐old psychiatric patient.…”
mentioning
confidence: 93%